Divided we stand : American workers and the struggle for Black equality - Nelson, Bruce, 1940-2022. (Princeton : Princeton University Press, 2001)
"Divided We Stand is a study of how class and race have intersected in American society - above all, in the "making" and remaking of the American working class in the nineteenth and twentieth centuries. Focusing mainly on longshoremen in the ports of New York, New Orleans, and Los Angeles, and on steelworkers in many of the nation's steel towns, it examines how European immigrants became American and "white" in the crucible of the industrial workplace and the ethnic working-class neighborhood."
"Divided We Stand includes vivid examples of white working-class "agency" in the construction of racially discriminatory employment structures. But Nelson is less concerned with racism as such, than with the concrete historical circumstances in which racialized class identities emerged and developed. This leads him to a detailed and often fascinating consideration of white working-class ethnicity, but also to a careful analysis of black workers - their conditions of work, their aspirations and identities, their struggles for equality. Making its case with passion and clarity, Divided We Stand will be a compelling and controversial book."--Jacket
Introduction: "Something in the 'atmosphere' of America" -- pt. 1. Longshoremen -- The logic and limits of solidarity, 1850s-1920s -- New York: "They ... helped to create themselves out of what they found around them" -- Waterfront unionism and "race solidarity": from the Crescent City to the City of Angels -- pt. 2. Steelworkers -- Ethnicity and race in steel's nonunion era -- "Regardless of creed, color, or nationality": steelworkers and civil rights (I) -- "We are determined to secure justice now": steelworkers and civil rights (II) -- "The steel was hot, the jobs were dirty, and it was war": class, race, and working-class agency in Youngstown -- Epilogue: "Other energies, other dreams": toward a new labor movement.
Includes bibliographical references and index.
Print version record.
JSTOR
Keywords: African Americans -- Employment -- History; Minorities -- Employment -- United States -- History; Foreign workers -- United States -- History; Discrimination in employment -- United States -- History; Race discrimination -- United States -- History; African American iron and steel workers -- History; African American stevedores -- History; African Americans -- Employment; Minorities -- Employment; Foreign workers; Discrimination in employment; Race discrimination; African American iron and steel workers; African American stevedores; Noirs américains -- Travail; Minorités -- Travail; Travailleurs étrangers.; Discrimination dans l'emploi.; Discrimination raciale; Travailleurs du fer et de l'acier noirs américains.; Débardeurs noirs américains.; Noirs américains -- Travail -- Histoire; Minorités -- Travail -- États-Unis -- Histoire; Travailleurs du fer et de l'acier noirs américains -- Histoire; Débardeurs noirs américains -- Histoire; Travailleurs étrangers -- États-Unis -- Histoire; racial discrimination; 71.62 ethnic relations (sociology); 85.63 industrial relations; HISTORY -- United States -- 20th Century; African American iron and steel workers; African American stevedores; African Americans -- Employment; Discrimination in employment; Foreign workers; Minorities -- Employment; Race discrimination; United States; Arbeitsmarktpolitik; Schwarze; USA; Rassendiskriminierung; Beschäftigung; Gewerkschaft; Schwärze; Vakverenigingen; Rassendiscriminatie; African Americans -- Employment -- History; Minorities -- Employment -- United States -- History; Foreign workers -- United States -- History; Discrimination in employment -- United States -- History; Race discrimination -- United States -- History; African American iron and steel workers -- History; African American stevedores -- History; Industrie sidérurgique -- Personnel -- États-Unis -- Histoire; Dockers -- États-Unis -- Histoire; Noirs américains -- Ségrégation -- États-Unis -- Histoire; Noirs américains -- Travail -- États-Unis -- Histoire; Minorités -- Travail -- États-Unis -- Histoire; Discrimination dans l'emploi -- États-Unis -- Histoire